2014
DOI: 10.1186/1759-8753-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ploidy level on the distribution of Pokey element insertions in the Daphnia pulex complex

Abstract: BackgroundTransposable elements (TEs) play a major role in genome evolution. Their capacity to move and/or multiply in the genome of their host may have profound impacts on phenotypes and dramatic consequences on genome structure. The population dynamics and distribution of TEs are influenced by their mode of transposition, the availability of niches in host genomes, and host population dynamics. Theories predict an increase in the number of TE insertions following hybridization or polyploidization. Evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 95 publications
0
34
0
Order By: Relevance
“…buzzatii ( Fig 6A ). Thus, the maternal cytoplasm could indeed be less efficient in silencing Helena expression and might cause the extensive presence of Helena transcripts noted in F1 and BC1 ovaries of young females ( Fig 5 ) [ 51 ]. Interestingly, there was an atypical Helena expression pattern including ovary follicular cells in F1 hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…buzzatii ( Fig 6A ). Thus, the maternal cytoplasm could indeed be less efficient in silencing Helena expression and might cause the extensive presence of Helena transcripts noted in F1 and BC1 ovaries of young females ( Fig 5 ) [ 51 ]. Interestingly, there was an atypical Helena expression pattern including ovary follicular cells in F1 hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…Meganucleases, and their associated introns and inteins, are encoded within phage, prokaryotes and single-cell eukaryotes. They recognize long DNA target sites ( 7 ): meganucleases from the LAGLIDADG protein family (reviewed in ( 8 )) typically recognize and cleave DNA targets spanning 20–22 base pairs in length. The length of their targets provides sufficient specificity to avoid toxicity to their host organism, while their ability to tolerate polymorphisms within those targets allows them to remain active when encountering genetic drift within their host genes ( 9 ).…”
mentioning
confidence: 99%
“…A recent analysis has demonstrated that even when maintaining up to 50% amino acid sequence identity and very close structural similarity, homologous wild-type meganucleases can recognize and cleave highly diverged DNA targets ( 10 ). The ability of these endonucleases to readily adopt new DNA target specificities, with minimal resculpting of their overall folded topology and structure, may reflect their biological function as the enzymatic drivers of intron mobility, transfer and persistence (reviewed in ( 7 )).…”
mentioning
confidence: 99%
“…Homing endonucleases, also termed ‘meganucleases’, are highly specific DNA cleaving enzymes, encoded by mobile open reading frames, that are present within all microbial life as well as in mitochondria and chloroplasts (Stoddard, 2014). Meganuclease genes are mobilized as a result of the DNA cleavage activity of their gene products.…”
Section: Introductionmentioning
confidence: 99%